HUBUNGAN PELAYANAN ANTENATAL CARE (ANC) DENGAN KEJADIAN PREEKLAMPSIA IBU HAMIL DI RSUD ULIN BANJARMASIN - Isnanda, Ernina Puspa; Noor, Meitria Syahadatina; Musafaah, Musafaah (Universitas Lambung Mangkurat, 2014)
Preeclampsia is one of the major causes of maternal mortality in the field of obstetrics. Predisposing factors that influence the incidence of preeclampsia include Antenatal Care (ANC) service. This study aims to determine the relationship between the ANC service in the incidence of preeclampsia in Ulin Hospital Banjarmasin the time periods from March to May 2012. This study is an observational analytic method with a cross sectional approach and collected the samplings with purposive sampling. Found total of 62 respondents consisted of 36 preeclampsia, routine ANC 55.56% and non-routine ANC 44.44%, and 26 none of preeclampsia, routine ANC 92.31% and non-routine ANC 7.69%. Analysis of Chi Square test at confidence level 95%, found the value of p value=0.004 (p <0.05) with OR 9.6. Based on the results of this study concluded that there is a relationship between the incidence of preeclampsia ANC services in the delivery room Ulin Hospital Banjarmasin the period from March to May 2012.Â Keywords: preeclampsia, ANC, routine